Fibrinogen, factor XIII and α2-antiplasmin genotypes are associated with inflammatory activity and anti-citrullinated protein antibodies. Issue 191 (July 2020) - Hoppe, Berthold; Schwedler, Christian; Edelmann, Anke; Pistioli, Anneta; Poddubnyy, Denis; Burmester, Gerd-Rüdiger; Häupl, Thomas
Abstract: Background: Fibrin(ogen) derivatives, crosslinked fibrin and fibrinolysis play important roles in inflammation and are involved in pathogenesis of rheumatoid arthritis (RA). About 2/3 of RA patients exhibit anti-citrullinated protein antibodies (ACPA) that target deiminated fibrinogen. Genetic variants of β-fibrinogen (FGB) (rs1800790G>A) and factor XIII A-subunit (F13A) Val34Leu (rs5985) are known to influence interactively inflammatory processes. It is hypothesized that predisposition for dense fibrin clots is related to better inflammation control. Methods: To test this hypothetical model a cohort of 924 patients (288 RA and 636 non-RA patients) (3545 observations) was genotyped for FGB (rs1800790G>A, rs1800788C>T), α-fibrinogen (FGA) (rs6050A>G, rs2070006G>A, rs2070016T>C), γ-fibrinogen (FGG) (rs1049636T>C), F13A Val34Leu (rs5985) and α2 -antiplasmin (A2AP) Arg6Trp (rs2070863). Genotype constellations potentially predisposing for dense fibrin clots were defined and their relation to inflammatory activity as measured by C-reactive protein (CRP) and disease activity score of 28 joints (DAS28) was assessed in univariate and multivariate analyses. The relation of these genotype constellations with presence of ACPA was tested. Results: Genotype constellations involving FGB rs1800790G>A and FGA rs2070016T>C were inversely associated with CRP levels (≥10 mg/L) (OR: 0.49, P  < 10 −8 /7adj  = 0.0001; OR: 0.52, P  < 0.0005/ P adj  = 0.01). In RA, both genotype constellations were observed with higher frequencies of low disease activity (DAS28 ≤ 3.2) (OR: 2.66, P  = .009; OR 2.78, P  = .01) and lower frequencies of high disease activity (DAS28>5.1) (OR: 0.52, P  < .03, OR: 0.42, P  = .01). Associations with CRP depended on A2AP 6Arg/Arg genotype known to be necessary for optimal anti-fibrinolytic capacity ( P  = .001). Finally, Genotype constellations involving FGB rs1800790G>A and FGA rs2070016T>C were found to be associated with ACPA-positivity in RA (OR: 2.18, P  < .03; OR: 1.95, P  = .09). Conclusions: These results support the hypothesis that genotypes, which increase fibrin clot density and anti-fibrinolytic capacity, reduce inflammatory activity and are related to humoral autoimmunity in RA. Graphical abstract: Unlabelled Image Highlights: Highly frequent fibrinogen genotypes are associated with inflammatory activity. Highly frequent factor XIII and α2-antiplasmin genotypes seem to contribute to this relation. Predisposition for high fibrin clot density and anti-fibrinolytic capacity seem to be related to low inflammatory activity. Genotypes predisposing for dense fibrin clots are associated with anti-citrullinated protein antibodies specific for RA.